Implementasi Pelaksanaan Pembelajaran pada Kurikulum Merdeka untuk Guru dan Siswa Kelas X di MAN 1 Aceh Tenggara Tahun Pelajaran 2024/2025 - Hartono, Makmur; Masnidar, Masnidar (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
The Kurikulum Merdeka (Independent Curriculum) was officially introduced by the Ministry of Education and Culture to provide greater flexibility for teachers and students in the learning process through differentiated instruction and competency-based assessment. This study aims to analyze the implementation of the Kurikulum Merdeka in Physics education for Grade X students at MAN 1 Aceh Tenggara and identify the challenges faced by teachers and students during its execution. A qualitative descriptive research approach was employed, utilizing data collection techniques such as classroom observations, interviews with teachers and students, questionnaire distribution, and documentation of the learning process. The findings indicate that teachers have successfully implemented the Kurikulum Merdeka by integrating Project-Based Learning (PBL), designing Capaian Pembelajaran (CP) or Learning Outcomes, and involving students in structuring the Alur Tujuan Pembelajaran (ATP) or Learning Objective Pathway, along with the development of teaching modules. However, several challenges persist, including low student engagement in project execution, ineffective time management for planned projects, and difficulties in implementing comprehensive learning assessments. Despite these challenges, the overall implementation of the Kurikulum Merdeka in Physics education at MAN 1 Aceh Tenggara has been well-executed, offering students a more flexible and meaningful learning experience.